AEROFEST BRINGS TOGETHER AEROSPACE ENGINEERING STUDENTS FROM SIX PUBLIC UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, December 2015 The aerospace festival, better known as AEROFEST, at the Universiti Sains Malaysia (USM) Engineering Campus held here recently has provided an avenue for more than 150 students in the fields of aerospace, aeronautics and astronautics from six public higher education institutions (IPTA) to meet and share ideas, information and experiences in representing their respective universities.